Information Technology Governance of UMKM in Kasasiur Banjar - Rismawati; Rasati, Adinda; Hardianti, Siti Gadis (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
One form of information technology management for UMKM in order to expand business networks, marketing and carrying out business processes is the use of the Cobit 5 framework. The benefits and maturity level of IT management are benchmarks for the direction of development and utilization strategies for UMKM. The purpose of this study was to assess the position of Kasasiur Banjar SMEs regarding implementation and targets to be achieved in the future. The result of the assessment is the maturity level of the current IT management position (existing). Furthermore, maturity targets will be determined for each selected IT process to be used as guidelines for the Kasasiur Banjar UMKM group in IT utilization. Maturity level assessment uses the domains EDM3, EDM4, APO7, DSS3, DSS6, and MEA1 with the calculation model referring to ISO/IEC 15504. Assessment results Maturity level related to IT development strategy is at level 1 (1.21), which is Performed. This means that Kasasiur Banjar SMEs have a concern for good IT management and processes have been implemented and achieved goals. The direction of governance development in UMKM Kasasiur Banjar is targeted to reach level 5, namely Optimizing.